2015
DOI: 10.1051/mfreview/2015003
|View full text |Cite
|
Sign up to set email alerts
|

Micro-deformation behavior in micro-compression with high-purity aluminum processed by ECAP

Abstract: -Ultrafine-grained (UFG) materials have a potential for applications in micro-forming since grain size appears to be the dominant factor which determines the limiting size of the geometrical features. In this research, high-purity Al was processed by equal-channel angular pressing (ECAP) at room temperature through 1-8 passes. Analysis shows that processing by ECAP produces a UFG structure with a grain size of~1.3 lm and with microhardness and microstructural homogeneity. Micro-compression testing was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…An annealing treatment was performed at a temperature of 773 K for 1 h by furnace cooling, and then the ECAP processing was conducted at RT using a die with an internal angle of 90° through eight passes using processing route B c as shown in Figure 1 a. A UFG pure Al was obtained with an average grain size of ~1.3 µm [ 29 ]. Following ECAP processing, micro-compression billets were prepared by micro-forward extrusion with a dimensional tool of 2 mm in diameter at room temperature.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…An annealing treatment was performed at a temperature of 773 K for 1 h by furnace cooling, and then the ECAP processing was conducted at RT using a die with an internal angle of 90° through eight passes using processing route B c as shown in Figure 1 a. A UFG pure Al was obtained with an average grain size of ~1.3 µm [ 29 ]. Following ECAP processing, micro-compression billets were prepared by micro-forward extrusion with a dimensional tool of 2 mm in diameter at room temperature.…”
Section: Experimental Materials and Proceduresmentioning
confidence: 99%
“…At present, experiments on UFG pure Al processed by ECAP through 8 passes with an average grain size of 1.3 m confirmed that the geometries and surface quality of the compressed samples can be improved by comparison with coarse-grained pure Al [26]. The UFG pure Al has been successfully applied to fabricate micro-turbine using micro-forming at room temperature [27].…”
Section: Matec Web Of Conferencesmentioning
confidence: 73%
“…Imposing a short term anneal of 10 minutes after the HPT processing has a significant effect on the microstructure and tensile properties of the HPT-processed specimens. There exists an optimum condition for the Al-1% Mg alloy by processing using HPT at room temperature and then giving the material a short anneal for 10 minutes at 423 K. Pure aluminium processed by ECAP to 8 passes produced materials with an average grain size of 1.3 m and this has been successfully applied to micro-forming of micro-turbine parts [17,18]. It was 07002-p. 5 reported that the geometries and surface quality of the compressed samples can be improved using UFG pure Al processed by ECAP through 8 passes by comparison with coarse-grained pure Al [18].…”
Section: Discussionmentioning
confidence: 99%
“…There is only limited research on the application of SPD processed materials in micro-forming [6,[15][16][17][18]. Therefore, experiments were conducted to investigate HPT processing of an Al-1% Mg alloy and to develop a processing route to improve the material ductility after SPD processing in order to attain a material suitable for micro-forming applications.…”
Section: Introductionmentioning
confidence: 99%